Evaluating the clinical efficacy of Guggulu resin on constipation: A randomised clinical trial. Issue 3 (December 2016) - Yousefi, Mahdi; Hoseini, Seyed Mousalreza; Salari, Roshanak
Abstract: Background: Chronic constipation is one of the most common clinical complaints. Numerous treatment methods have been proposed for the treatment of chronic constipation, including those from traditional and complementary medicine. One of the common drugs used for chronic constipation in traditional Persian medicine with laxative effects is Guggulu ( Commiphora mukul l. ) resin. The clinical effects of Guggulu on functional constipation are evaluated in this study. Methods: This controlled clinical trial study was carried out in 103 outpatients with functional constipation based on the ROME III criteria. Patients were randomly divided into two groups. The control group was given oral administration of lactulose syrup daily at a laxative dose for one month, and the intervention group were given Guggulu resin 3 g daily in 3 divided doses for one month. Intensity and frequency of constipation were assessed before, during and at the end of the intervention period, and one month after termination of intervention. Results: There was no significant difference in the intensity and frequency of constipation between the two groups at baseline ( P  = 0.755). In the second week constipation severity decreased in both groups, but because of more reduction in the control group, the difference between two groups was statistically significant ( P  < 0.001). One month after treatment, the difference between two groups was not significant ( P  = 0.93). In both groups the severity of constipation increased one month after the cessation of the intervention, with constipation severity significantly higher in the control group than in the intervention group ( P  < 0.001). The same pattern was observed in frequency of constipation. Conclusion: This study suggests that Guggulu resin may have a role as an alternative treatment in chronic functional constipation, although further studies are required to confirm efficacy.